(untitled) (Atti del Sodalizio Glottologico Milanese, 2021)
‘As salt (melts) in water’: a formula between magic and medicine: among similia similibus formulae. The solvability of salt does not only offer an image of great impact but also fulfils to the needs of those who wish the total annihilation of someone or something considered to be an enemy both in the field of ‘private’ communication (defixiones) and of ‘public’ communication (medical formulas). In four defixiones we find the comparative introduced by ut, a[d qu]em modum, comodo + sal in/et aqua, the same formula (liquescas tamquam salis in aqua) used by Marcellus Empiricus to eliminate gland-related diseases through the recitation of a carmen mirum. Among the phenomena that deal with defissory formulae and medical formulae, including the specific use of several verbs, this figure similia similibus does not allude to a magical praxis but to the knowledge of the phenomenon as such.